A novel bandgap voltage reference based on folding compensation. Issue 8 (15th April 2023) - Liu, Mingyu; Zhuang, Haoyu; Huang, Liangchen; Tao, Linzhi; Li, Qiang
Abstract: This letter proposes a novel bandgap reference circuit that utilizes both curvature and folding compensation to achieve a temperature coefficient (TC) of 2.23 ppm/°C. Unlike traditional BGRs, the unique folding compensation method of this circuit improves the performance at low temperature and can also be applied within a specific temperature range. Abstract : This letter proposes a novel bandgap reference circuit that utilizes both curvature and folding compensation to achieve temperature coefficient (TC) of 2.23 ppm/°C.